Relationship between test of postural control and strength and ability tests in basketball players - Asadi, A.; Arazi, H. (Revista Internacional de Ciencias del Deporte, 2018)
This study investigated the relationship between performance tests (i.e., jumping ability, strength, sprint and change of direction ability) and dynamic postural control in young basketball players. Twenty-three young basketball players participated in this study and performed measurements of dynamic balance (Star Excursion Balance Test [SEBT]), countermovement jump (CMJ), broad long jump (BLJ), 4×9-m shuttle run, agility T test (TT), Illinois agility test (IAT), 20-m sprint and lower extremity muscle strength. Significant association was observed between balance (at medial direction) and strength performance (r = 0.523, p < 0.05). Significant positive correlations were detected between directions of SEBT and BLJ (r = -0.466 to -0.479, p < 0.05), 4×9-m shuttle run (r = -0.403 to 0.486, p < 0.05), TT (r = -0.410, p < 0.05), IAT (r = 0.435, p < 0.05) and sprint (r = -0.402 to 0.452, p < 0.05). Postural control is more in relation to change of direction ability, sprint and power performance in basketball athletes.